Economic Leading Indicators for Tracking Singapore's Growth Cycle - Chow, Hwee Kwan (Institutional Knowledge at Singapore Management University, 1995)
This paper attempts to develop a set of economic leading indicators which can be used for monitoring the growth cycle of Singapore. A time series approach based on the construction of cross correlation functions is used to check that individual series presage activity over the growth cycle. Due to the counter-cyclical pattern exhibited by the output of the construction sector (GDPC), the latter is treated separately from the value-added of the rest of the economy (GDPNC). ultimately, five series are found to exhibit good leading behaviour over GDPC. We obtain substantial gain over pure time series models when using these indicators in economic forecasting.